The relationship of diabetes mellitus diet with blood sugar level control in inpatients at PKU Muhammadiyah Gamping Hospital Yogyakarta - Widiyatmoko, Agus; Adristi, Ristyaning Safa (Institute of Computer Science (IOCS), 2024)
The high incidence of type 2 diabetes mellitus is caused by several factors. One way to reduce the incidence of type 2 diabetes mellitus is to undergo nutritional therapy or a diabetes mellitus diet so that patients can avoid various complications of diabetes mellitus that lead to death. This study was conducted by interviews using a food recall form and using medical record data to see the patient’s blood sugar levels before breakfast, lunch and evening. The sample of this study consisted of 39 respondents. The data obtained were analyzed using the chi square & T-test statistical test. The results showed that most respondents were aged 44-58 years (56.4%), female gender was more dominant (53.8%). The results obtained on energy, carbohydrate, protein and fat intake were not significant with p values> 0.05. Meanwhile, the T-test results showed a significant difference between the average blood sugar levels of patients with sufficient and insufficient energy intake with a p value 0.023. However, there was no significant difference between the average blood sugar levels of patients with carbohydrate, protein and fat intake with insufficient and sufficient intake with p values> 0.05. There is no significant difference between energy, carbohydrate, fat and protein intake on blood sugar levels of inpatients at PKU Muhammadiyah Gamping Hospital.